Problematika Pendidikan Inklusi di Sekolah - Sudjak Sudjak (MODELING: Jurnal Program Studi PGMI, 2018)
The declaration of inclusive education focused on facilitating the needs of special needs children education has been running in many areas of Indonesia, especially in big cities. However, the implementation of inclusive education is not without constraints and problems. There are many problems found. The purpose of this article is to explain the problems found in the implementation of inclusive education. The research method used is qualitative research and descriptive research type. The results of the study indicate the existence of various problems found in the implementation of inclusive education, including inclusive understanding and implications, organizational school policy, learning process, teacher condition and support system.